Knowledge of Dentists in Tertiary Institutions on the Use of Clear Aligners as a Means of Orthodontic Treatment - Ojebor, Hillary; Onyia, Nonso; Chukwumah, Nneka; Nwafor, Ikenna; Olubamiwa, Tolulope (Nigerian Journal of Basic and Clinical Sciences, 2025)
Context:Clear aligner therapy (CAT) is a rapidly growing, patient-friendly, and compliance-oriented orthodontic modality. Its adoption in Nigeria remains limited, primarily due to higher costs compared to conventional fixed orthodontic treatments. Aims:To assess Nigerian dentists’ knowledge regarding the use and applications of CAT in orthodontic practice. Settings and Design:A cross-sectional analytical study conducted among dentists of various specialties and cadres practicing across all regions of Nigeria. Materials and Methods:Data were collected via a pretested, self-administered online questionnaire (Google Form) consisting of yes/no and Likert-scale items. Statistical analysis was performed using SPSS version 21. Categorical data were summarized as frequencies and percentages, while numerical data were presented as means ± standard deviations. Group differences were evaluated using the Kruskal-Wallis test with post hoc comparisons, associations were assessed using Spearman’s rank correlation, and predictors of knowledge were identified via binary logistic regression. Statistical significance was set at p < 0.05. Results:A total of 161 dentists from various tertiary health centers participated, with a mean age of 33.12 ± 4.89 years. Most respondents were aged 31–40 years (62.7%) and male (70.0%). The majority were registrars (54.0%), while dental officers were the least represented (9.9%). Participants included oral surgeons (23.6%), general practitioners (14.3%), and other dental specialties. Half of the respondents (50.9%) practiced in the midwestern region, while the eastern region was least represented (9.9%). Using a baseline knowledge score of 24.67 from orthodontic senior registrars, only 21.1% of participants demonstrated good knowledge of CAT. Knowledge scores varied significantly by age (p = 0.024), rank (p = 0.036), specialty (p = 0.001), and years of experience (p = 0.003). Binary logistic regression identified specialty as the only significant predictor of knowledge (p = 0.005), with orthodontic residents having significantly higher knowledge than other residents. Conclusion:Despite its global popularity, knowledge and use of CAT among Nigerian dentists remain limited. Integrating CAT into dental curricula, workshops, and research initiatives is critical to enhance awareness, improve adoption, and align orthodontic practices in Nigeria with international standards.